Research Trend in The Inhibition of Transient Receptor Potential Vanilloid 1 (TRPV1): Bibliometric Analysis and Visualization - Shereen M. Aleidi, Amani A. Harb, Lina A. Dahabiyeh, Montaha AL-Iede, Islam Hamad, Walhan Alshaer, Ihab M. Almasri, Yasser Bustanji (Journal of Applied Pharmaceutical Science, 2024)
This study aimed to provide a comprehensive overview of the research trend in transient receptor potential vanilloid 1 (TRPV1) inhibition and modulation. A bibliometric analysis of peer-reviewed articles and reviews published from 2003 until 2022 in the Scopus database was conducted. A total of 7,470 publications were retrieved and distributed over 140 countries and published by 23,875 authors. The number of publications was increasing over the determined period, indicating a steady upward trend. Approximately 80% of the total extracted publications were research articles. The leading country in this research field is the United States of America. The top publishing journal was the British Journal of Pharmacology. The most frequent keywords included TRPV1, pain, and capsaicin. Analysis of authors-keywords pointed to the role of TRPV1 inhibition in numerous conditions including cancer, inflammation, oxidative stress, pruritus, osteoarthritis, migraine, the endocannabinoid system, nitric oxide, and endothelium relaxation. This study revealed most of the research was focused on the role of TRPV1 channels in pain. However, TRPV1 has been implicated in different pathological conditions. This implication should be translated into the development of therapeutic strategy, and efforts should be expanded into new clinical indications and novel drug discovery.
Keywords: TRPV1, capsaicin, pain, inhibition, bibliometrics and visualization